2015
DOI: 10.3233/jbr-150095
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTL associated with flower and runner production in octoploid strawberry (Fragaria×ananassa)

Abstract: BACKGROUND: Understanding the genetics of flowering in the strawberry (Fragaria × ananassa) will aid in the development of breeding strategies. OBJECTIVE: To search for quantitative trait loci (QTL) associated with remontancy and weeks of flowering in the strawberry. METHODS: Previously collected phenotypic data from two non-remontant 'Honeoye' × remontant 'Tribute' strawberry populations and simple sequence repeats (SSR) markers were used to search for QTL associated with repeat flowering, weeks of flowering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…15 was further confirmed by Sooriyapathirana et al . 33 using an extended population. Using three separate Japanese population, Honjo et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 was further confirmed by Sooriyapathirana et al . 33 using an extended population. Using three separate Japanese population, Honjo et al .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have constructed linkage maps using different suite of molecular markers such as RAPD, AFLP and SSR, etc. 2732 and few of those studies reported QTLs with various additive effects for PF and RU traits in cultivated strawberry 3,4,15,17,3335 . However, these markers largely suffer from either non-transferability across investigations, insufficient genome-wide coverage, poor density or higher developmental and screening costs 3,15,36 .…”
Section: Introductionmentioning
confidence: 99%
“…The strawberry samples analyzed in this study consisted of: parents and 24 offspring from the ‘Holiday’ × ‘Korona’ population from the Netherlands ( Van Dijk et al, 2014 ); parents and 60 seedlings from the ‘Tribute’ × ‘Honeoye’ population from Michigan State University (MSU) ( Castro & Lewers, 2016 ; Sooriyapathirana et al, 2015 ); parents and 51 offspring from the ‘Redgauntlet’ × ‘Hapil’ population from East Malling Research, UK ( Sargent et al, 2012 ; Table S1 ). DNA was extracted from actively growing leaf tissue with the E-Z 96® Plant DNA extraction kit (Omega BioTek, Norcross, GA, USA) as previously described ( Gilmore, Bassil & Hummer, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…The development of molecular tools for cultivated strawberry has been hindered in the past by its allo-octoploid (2 n = 8 × = 56) genetic constitution, limiting the development of dense linkage maps and high-throughput marker resources ( Sargent et al 2009 ). For this reason, only a few studies have reported major genes and QTL in cultivated strawberry to date ( Van de Weg 1997a , b ; Haymes et al 1997 , 2000 ; Weebadde et al 2008 ; Zorrilla-Fontanesi et al 2011 , 2012 ; Lerceteau-Köhler et al 2012 ; Antanaviciute et al 2015 ; Sooriyapathirana et al 2015 ; Roach et al 2016 ). However, the sequencing of the diploid woodland strawberry ( F. vesca ) genome ( Shulaev et al 2011 ) set the stage for the development of the Affymetrix IStraw90 Axiom array, a 90 K SNP array for octoploid strawberry ( Bassil et al 2015 ).…”
mentioning
confidence: 99%